2017
DOI: 10.1590/0037-8682-0410-2016
|View full text |Cite
|
Sign up to set email alerts
|

A fatal case of tuberculous meningitis in a child with juvenile idiopathic arthritis: a diagnostic challenge

Abstract: The prognosis of tuberculous meningitis, a rare form of extrapulmonary tuberculosis, depends on the stage of treatment initiation. We report a fatal case of tuberculous meningitis. The patient had received successive tumor necrosis factor (TNF) antagonists and abatacept to treat juvenile idiopathic arthritis, with negative results for polymerase chain reaction and acid-fast bacilli on smear, had normal cerebrospinal fluid (CSF) adenosine deaminase and glucose levels. Six weeks post-admission, the CSF culture d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
1
8
0
1
Order By: Relevance
“…Our study highlights the great severity of TB disease in children on anti-TNF-α therapy, consistent with previous case reports [10,[13][14][15][16]. All patients captured by our study presented with severe disease.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study highlights the great severity of TB disease in children on anti-TNF-α therapy, consistent with previous case reports [10,[13][14][15][16]. All patients captured by our study presented with severe disease.…”
Section: Discussionsupporting
confidence: 91%
“…To our knowledge, fewer than 20 cases have been described in detail in the peer-reviewed literature so far [10][11][12][13][14][15][16]. Concerningly, several of those cases had a fatal outcome.…”
Section: Introductionmentioning
confidence: 95%
“…This patient was admitted to ITU and was commenced on anti tuberculous therapy however did not survive. His sputum cultures initially were negative and another sample in week 6 was positive for mycobacterium tuberculosis that was responsive to antituberculous therapy [13].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 18 patients who were alive at presentation, 14 had miliary TB, and 4 had central nervous system involvement, both of which are associated with high levels of morbidity and mortality [25,26]. This predilection for severe TB manifestations in children on anti-TNF-α treatment is further documented by several case reports and small case series [27,28]. Notably, the aforementioned study also showed those children typically require prolonged TB treatment (median duration: 50 weeks), and that the risk of long-term sequelae in this patient population is substantial (observed in 28% of the survivors).…”
Section: Discussionmentioning
confidence: 99%